APPRECIATION AND THE STATUTES. - Lundahl, Melvin O. (The Accounting Review, 1932)
Despite the fact that business enterprises are experiencing a period of falling prices and costs, the question of whether or not surplus arising from unrealized appreciation of assets is available for dividends is still important. It is of the utmost importance that law and accounting be in agreement in regard to the treatment of a problem of this sort so that the business man can be advised not only as to the logical procedure to be followed, but as to its legality as well. The profit-and-loss-statement group consists of eighteen states whose statutes state that dividends cannot be paid except from surplus profits of the business. Here also courts have had much difficulty in interpreting the statutes, for, in certain cases in this group, it has been made to appear that unrealized appreciation is available for dividends, because appreciation has been included in profits. This occurs when profits are conceived to be the net increase in wealth during a period, that is when assets are valued at present worth and not at cost. Six states give directors of a corporation the option of paying dividends from whatever source they choose, namely, profits or the excess of assets over liabilities and capital stock.